Solubility of camphene and caryophyllene oxide in subcritical and supercritical carbon dioxide - Yeoh, Hooi S.; Choong, Thomas S. Y.; Mohd Adzahan, Noranizan; Abdul Rahman, Russly; Chong, Gun H. (Faculty of Engineering, Chulalongkorn University, 2015)
The solubility of camphene and caryophyllene oxide in subcritical and supercritical carbon dioxide were determined using dynamic off-line analysis method. Under subcritical condition, solubility of camphene and caryophyllene oxide were (1.738 to 18.118) ∙ 10-3 and (1.84 to 7.872) ∙ 10-3 respectively at 298.15 K with pressure varied from 50 to 70 bar. At 302.15 K and under same pressure variation, solubility of camphene and caryophyllene oxide were (1.918 to 18.76) ∙ 10-3 and (14 to 25.624) ∙ 10-3 respectively. Under supercritical condition, experiments were run from 80 bar to 250 bar. Solubility of camphene was ranged from (54.024 to 151.67) ∙ 10-3 at 308.15K and (17.552 to 65.487) ∙ 10-3 at 313.15 K; while solubility of caryophyllene oxide was ranged from (24.9 to 299.94) ∙ 10-3 at 308.15 K and (2.542 to 102.359) ∙ 10-3 at 318.15 K. These solubility data was correlated with three semi-empirical models which were Bartle, Chrastil and Mendez-Santiago-Teja model. Of these three models, Mendez-Santiago-Teja model showed excellent fitting with average absolute relative deviation kept below 2%.